WOMEN’S RIGHTS IN THE POLITICAL SPHERE- MACEDONIAN AND INTERNATIONAL EXPERIENCE - Dana Nikolov (Journal of Process Management and New Technologies, 2015)
Gender equality is a key issue that concernsall government entities in the world and the extent of its legal regulation depends on the inclusion of women in the political sphere of a state. Early women's rights movement dates back to the 1830s when women began speaking publicly against slavery. Since then, the performance by women on the legal and political scene is in continuous progression, but it is not sufficient. Currently the country with the largest number of women in political office is Rwanda, holding the world record with 64% representation. Other countries where women's inclusion in politics is high are the Scandinavian countries, led by Sweden. Contrary to the positive tendency in these two countries concerning this issue, there are those which are first inthe non-participationof women in the political sphere, like Ukraine with 10%, Lebanon and Iran 3% and 0.3% in Yemen. When it comes to gender equality in the Republic of Macedonia, equal opportunities for women and men are guaranteed mainly by the Constitution of the Republic of Macedonia as the highest legal act, but also by a large number of laws that prohibit discrimination based on gender. The participation of women in the parliament of Macedonia for the last parliamentary term (2011- 2014) was 34.14%. Raising concern is the women’s under-representation in the executive branch, and the Republic of Macedonia cannot claim to have any significant involvement of women in the diplomatic sphere either. Nevertheless, the efforts for a step closer towards increasing women's participation in the decision-making process will not cease.